Are the silicate crystallinities of oxygen-rich evolved stars related to their mass loss rates?. Issue Volume 14:Issue S343(2019) (August 2018) - Jiang, Biwei; Liu, Jiaming; Li, Aigen
Abstract: A sample of 28 oxygen-rich evolved stars is selected based on the presence of crystalline silicate emission features in their ISO/SWS spectra. The crystallinity, measured as the flux fraction of crystalline silicate features, is found not to be related to mass loss rate that is derived from fitting the spectral energy distribution.